LIVER FUNCTION AND BIOMARKERS OF OXIDATIVE STRESS LEVELS IN STREPTOZOTOCIN-INDUCED DIABETIC RATS TREATED WITH LEAVES EXTRACT OF CARICA PAPAYA - Igbashio, Mercy D.; Eluehike, N.; Oriakhi, K. (FUDMA JOURNAL OF SCIENCES, 2025)
Diabetes mellitus is defined an in adequate insulin secretion or activity. Oxidative stress brought on by both experimental and human diabetes can harm multiple organs, including the liver. The present study investigated the liver ameliorating and antioxidant effects of hydroethanol extract of matured (yellow) Carica papaya leaf on streptozotocin-induced diabetes. We randomly assigned a total of 48 adult male Wistar rats into six groups of eight rats each. Normal control, diabetic untreated, diabetic + metformin, diabetic + 250 mg/kg body weight extract, diabetic + 500 mg/kg, and diabetic + 750 mg/kg body weight extract. A type I model of diabetes was induced in the rats via intraperitoneal injection of 60 mg/kg body weight streptozotocin. Treatment lasted for 14 days. Biochemical assays such as alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, total and direct bilirubin, albumin, total protein and globulin were analyzed for liver function. Biomarkers of oxidative stress activity such as catalase, superoxide dimutase, glutathione reductase, glutathione peroxidase, and malondialdehyde were conducted using standard methods. Histopathological evaluation of the rats’ liver was also carried out. The results obtained revealed a significant improvement in the liver function and likewise the antioxidant levels of the diabetic rats treated with the plant extracts, which was further confirmed by the histology evaluation. This study suggests that hydroethanol extract of the mature (yellow) leaves of Carica papaya has liver damage ameliorating potentials and can enhance the antioxidant defense system in the liver of streptozotocin-induced diabetic rats.
Keywords: Carica papaya; Diabetes; Liver function; Matured leaves; Oxidative stress; Streptozotocin